The Effect of Self-Efficacy and Role Understanding on Teachers' Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR). Issue 5 (3rd September 2022) - Kuok, Angus C.H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana
ABSTRACT: This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers' perceptions about their roles and how they responded to inclusive practices in their school. Teachers' perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers' self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers' cognitive work engagement. Teachers' level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.